2018
DOI: 10.1016/j.rmed.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term respiratory muscle endurance training on respiratory and functional outcomes in patients with Myasthenia gravis

Abstract: Background: Myasthenia gravis (MG) is characterized by reduced muscle endurance and often leads to respiratory complications. Objective: A long-term respiratory muscle endurance training (RMET) based on normocapnic hyperpnea was introduced for the first time in MG patients. We investigated RMET effects on respiratory endurance (RE), MG symptoms, lung function and physical fitness and compared the results with a control group (CG). Methods: The training period consisted of four weeks intensive training (IT; fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
(74 reference statements)
0
17
0
Order By: Relevance
“…A multicenter randomized controlled trial is currently underway in Denmark to investigate the effect of breathing retraining on the impact on quality of life in poorly controlled asthmatics (148). In a small study (149), 12 MG patients underwent long-term respiratory muscle endurance training, which resulted in a change in their breathing pattern with prolonged expiration. Interestingly patients reported an improvement in their MG symptoms, in their respiratory symptoms and in their physical fitness.…”
Section: Dysfunctional Breathing In Myasthenia Gravismentioning
confidence: 99%
“…A multicenter randomized controlled trial is currently underway in Denmark to investigate the effect of breathing retraining on the impact on quality of life in poorly controlled asthmatics (148). In a small study (149), 12 MG patients underwent long-term respiratory muscle endurance training, which resulted in a change in their breathing pattern with prolonged expiration. Interestingly patients reported an improvement in their MG symptoms, in their respiratory symptoms and in their physical fitness.…”
Section: Dysfunctional Breathing In Myasthenia Gravismentioning
confidence: 99%
“…The training group participated in training of diaphragmatic breathing and pursed lips breathing and improved their respiratory muscle endurance, maximum inspiratory and expiratory pressures, and thoracic mobility in comparison with their own baseline levels and compared with controls (70). Smaller studies have shown the benefit of long-term respiratory muscle endurance training on lung function and respiratory endurance in mild to moderate MG (71,72).…”
Section: Respiratory Muscle Training In Mgmentioning
confidence: 99%
“…The main improvement items in MGC include swallowing and breathing. The effect of RMT in patients with MG has been shown in several previous reports [5,6]. Weakness and fatigue of respiratory muscles are responsible for dyspnea and reduced exercise tolerance and thus can compromise quality of life.…”
Section: Discussionmentioning
confidence: 86%
“…However, Fregonezi et al [7] state that using the interval-based inspiratory muscle training 3 times a week for 8 weeks did not show any changes in lung function in MG patients. A recent study shows that long-term (thirteen months) respiratory muscle endurance training significantly increased respiratory endurance measured as time until exhaustion (T lim ) to 412% of the baseline in MG patients [6]. This can be explained by the specificity of the training of different types of RMT [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation